2020
DOI: 10.1007/s11043-020-09476-8
|View full text |Cite
|
Sign up to set email alerts
|

Rheological-dynamical model of concrete and its application on RC beams

Abstract: An improved analytical model based on rheological-dynamical analogy (RDA) is briefly explained and used for the analysis of concrete cylinders under compression. The approach involves standard mechanical properties such as compressive strength, elastic modulus, concrete density and Poisson's ratio for the prediction of both the ascending and the descending branch of the stress-strain curve. Our own experimental data for arbitrarily selected high strength concrete with high deformability was analyzed. Further, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
(42 reference statements)
0
5
0
Order By: Relevance
“…A large number of experiments have shown that the degree of saturation affects the elastic properties of wet concrete and that the strength of saturated concrete decreases, while the modulus of elasticity of saturated concrete increases compared to dry samples (Wang and Li, 2007), (Zhou et al ., 2016) and (Milašinović et al ., 2022c).…”
Section: Model Verificationmentioning
confidence: 97%
See 1 more Smart Citation
“…A large number of experiments have shown that the degree of saturation affects the elastic properties of wet concrete and that the strength of saturated concrete decreases, while the modulus of elasticity of saturated concrete increases compared to dry samples (Wang and Li, 2007), (Zhou et al ., 2016) and (Milašinović et al ., 2022c).…”
Section: Model Verificationmentioning
confidence: 97%
“…A large number of experiments have shown that the degree of saturation affects the elastic properties of wet concrete and that the strength of saturated concrete decreases, while the modulus of elasticity of saturated concrete increases compared to dry samples (Wang and Li, 2007), (Zhou et al, 2016) and (Mila sinovi c et al, 2022c). Experimental data in Yaman et al (2002a) were obtained on concrete samples with different amounts of entrained air and different water-cement ratios.…”
Section: Modeling Of Dry and Wet Porous Concretementioning
confidence: 99%
“…Before any compressive strain reaches the value εc1 at the compressive strength fcS, the analysis is trivial. After the strain εc1 has been surpassed, the corresponding analysis is explained in Milašinović et al (2020a). In Figure 7, id is the depth of the compression zone, whereas d is the effective depth of the beam.…”
Section: Analysis Of Conventional Reinforced Concrete Framementioning
confidence: 99%
“…Dynamic properties of the concrete cylinders calculated by the resonance method in Section 4.1 indicate that compressive strength is reached when the damage variable D c is equal to 0.5, whereas the damage variable of D soft = 0.86 represents the lowest point on the softening branch of the quasi-static diagram (Milašinović et al , 2020a).…”
Section: Analysis Of Conventional Reinforced Concrete Framementioning
confidence: 99%
See 1 more Smart Citation